Chemotranscriptome analysis indicates the neurotrophic and neuromodulator effects of a citicoline molecule - I. Yu. Torshin; O. A. Gromova; L. V. Stakhovskaya; V. A. Semenov; I. A. Shchukin (Неврология, нейропсихиатрия, психосоматика, 2020)
Objective: to investigate the effect of citicoline (CTC) on gene transcription.Material and methods. Chemotranscriptome analysis of the CTC molecule was carried out on an NPC.TAK model, provided that the cells were incubated with CTC for 24 hours.Results and discussion. CTC dose-dependently affected the transcription of 8,838 out of 12,716 annotated human genes, mainly by increasing the transcription of the genes involved: 1) in the neurotransmitter metabolism of serotonin (n=36), dopamine (n=32), GABA (n=14), and acetylcholine (n=27); 2) in showing the effects of neurotrophic factors (n=152), including nerve growth factor (n=11); 3) in maintaining the cardiovascular system (vasodilation and cardiac electrical activity; a total of 76 genes). CTC reduced the transcription of the genes, whose protein activity supported inflammation (n=86) and cell division (n=656). CTC elevated the expression of 60 genes involved in triglyceride processing and decreased the expression of 51 genes whose proteins were involved in cholesterol metabolism. CTC increased the transcription of the genes involved in the body’s response to various drugs, including antiepileptic drugs (n=20), dopaminergic agents (n=19), antipsychotics (n=38), anxiolytics (n=21), sedatives (n=22), antidepressants (n=35), anesthetics (n=23), and antidementia drugs (n=11).Conclusion. Chemotranscriptome analysis indicated the positive effect of CTC on neurotransmission, neuroprotection, lipid profile, and a higher neuronal susceptibility to other neuroactive drugs.